2009
DOI: 10.2332/allergolint.08-oa-0058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pranlukast Hydrate on Airway Hyperresponsiveness in Non-Asthmatic Patients with Japanese Cedar Pollinosis

Abstract: The results indicate that pranlukast hydrate inhibits airway hyperresponsiveness in non-asthmatic patients with Japanese cedar pollinosis. In turn, this suggests that cysteinyl leukotrienes have a role in increased airway responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…38,45e47 Recently, Sagara et al showed that initial treatment with pranlukast plus mequitazine significantly suppressed exacerbation airway hyper-responsiveness during the pollen season in non-asthmatic patients with JCCP. 48 …”
Section: Pharmacotherapymentioning
confidence: 97%
“…38,45e47 Recently, Sagara et al showed that initial treatment with pranlukast plus mequitazine significantly suppressed exacerbation airway hyper-responsiveness during the pollen season in non-asthmatic patients with JCCP. 48 …”
Section: Pharmacotherapymentioning
confidence: 97%
“…The effectiveness of omalizumab on AR and Japanese cedar pollinosis was demonstrated as well as on asthma. 29,30 These data suggest that certain systemic drugs such as LTRAs and anti-IgE monoclonal antibody would produce better asthma-related outcomes in patients with asthma and concomitant AR.…”
Section: Treatment Strategy Of Asthma With Comorbid Ar or Japanese Cementioning
confidence: 97%
“…In several studies, pranlukast showed significant efficacy in reversing bronchoconstriction caused by various stimuli, including LTD 4 , dust mite, aspirin, exercise, and even alcohol (Abraham et Hamilton et al, 1998;Ishioka et al, 2000;Suguro et al, 2000;Yoshida et al, 2000b;Myou et al, 2001;Obase et al, 2001Obase et al, , 2002. Some other studies also showed the effectiveness of pranlukast in reducing bronchial hypersensitiveness, another important feature of asthma, caused by various factors (Nakamura et al, 1998;Ishioka et al, 2000;Yoshida et al, 2000a;Yamauchi et al, 2001;Sagara et al, 2009). Because the current first-line method for treating asthma is ICS or ICS plus LABAs, a number of recent studies tested whether pranlukast could provide additional clinical benefits when used with ICS or ICS plus LABAs.…”
Section: B Currently Used Leukotriene Receptor Antagonist Drugs and mentioning
confidence: 99%